2014
DOI: 10.7897/2230-8407.0511173
|View full text |Cite
|
Sign up to set email alerts
|

Gastro Protective and Antioxidant Effect of Euphorbia Prostrata Against Indomethacin Induced Gastric Ulcers in Healthy Adult Male Albino Rabbits

Abstract: Euphorbia prostrate belongs to family Euphorbiaceae locally known as Doodhi is small annual herb. Current study was conducted to evaluate the gastro protective and antioxidant effectiveness of the aerial parts of E. prostrata in indomethacin induced ulcer in adult male albino rabbits. A total 36 mice were taken and divided into 6 equal groups. At day 0 and 14 of experiment the blood sample was collected from each animal and serum was separated from blood which was used for the determination of Total oxidant st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
1
0
2
Order By: Relevance
“…A woman who had husbands in the age group ≤ 30 years old was 5 times more likely to report intimate partner physical violence than those who had husbands ≥ 41 years old. This result is in contrast with study finding in Hawzen, Ethiopia [25], in our finding as age of husband increasing experience of intimate partner physical violence decreases irrespective of women’s age, but in the study in Hawzen as women’s age increases the experience of intimate partner physical violence increases irrespective of husbands age, it was also in contrast with the report in WHO [14] and Iran [26].…”
Section: Main Textcontrasting
confidence: 99%
See 1 more Smart Citation
“…A woman who had husbands in the age group ≤ 30 years old was 5 times more likely to report intimate partner physical violence than those who had husbands ≥ 41 years old. This result is in contrast with study finding in Hawzen, Ethiopia [25], in our finding as age of husband increasing experience of intimate partner physical violence decreases irrespective of women’s age, but in the study in Hawzen as women’s age increases the experience of intimate partner physical violence increases irrespective of husbands age, it was also in contrast with the report in WHO [14] and Iran [26].…”
Section: Main Textcontrasting
confidence: 99%
“…Our Study finding also less than from the study conducted in Debre Tabor town in 2015, which showed, 56.1% lifetime and 27.9% in the last 12 months [23]. Additionally, another Study conducted in Shimelba refugee camp was 25.5% [12], and Southwest Ethiopia, 64.7% [24], Hawzen, 38.6% which is higher than our study finding [25].…”
Section: Main Textcontrasting
confidence: 83%
“…The mean value of A. parviflora at dose rate of 750 mg/kg was not significantly different from omeprazole. The results of our study conicide with other studies (Aslam et al, 2013;Begum et al, 2014). pH of gastric secretions was measured in the current study.…”
Section: Discussionsupporting
confidence: 91%